2005
DOI: 10.1164/rccm.200505-807oc
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide

Abstract: Acetazolamide, the first efficient pharmacologic treatment of chronic mountain sickness without adverse effects, reduces hypoventilation, which may be accentuated during sleep, and blunts erythropoiesis. Its low cost may allow wide development with a considerable positive impact on public health in high-altitude regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(21 citation statements)
references
References 31 publications
2
18
1
Order By: Relevance
“…Acetazolamide was discontinued at ~4300m (Pheriche), at least one day before ascending to the laboratory, to allow sufficient time (e.g., ≥48 hours) for the drug to clear participants' system prior to the first data collection session at 5050m 23,24 . Previously, pre-treatment of acetazolamide has resulted in an almost negligible difference of PASP (~2mmHg; no statistical analyses were performed) 48hours after final drug treatment when compared to individuals that received placebo treatment 25 .…”
Section: Study Participants and Designmentioning
confidence: 99%
“…Acetazolamide was discontinued at ~4300m (Pheriche), at least one day before ascending to the laboratory, to allow sufficient time (e.g., ≥48 hours) for the drug to clear participants' system prior to the first data collection session at 5050m 23,24 . Previously, pre-treatment of acetazolamide has resulted in an almost negligible difference of PASP (~2mmHg; no statistical analyses were performed) 48hours after final drug treatment when compared to individuals that received placebo treatment 25 .…”
Section: Study Participants and Designmentioning
confidence: 99%
“…The long-term use of respiratory stimulants, such as medroxyprogesterone [88] or acetazolamide [89-91], also improves oxygenation and polycythemia in CMS patients. Angiotensin-converting enzyme inhibitors such as enalapril may also be helpful [92,93].…”
Section: Respiratory Disorders Associated With Chronic Exposure To Himentioning
confidence: 99%
“…[22] Other studies from La Paz have reported similar rates of CMS with one study measuring a rate of 5.2%. [23] In Bolivia as a whole approximately two-thirds of the population live at altitudes greater than 3000 m and CMS is deemed a considerable public health problem. Studies there have found CMS rates between 8% and 10% in the male active population in the country.…”
Section: Discussionmentioning
confidence: 99%